Are there effects of a match between learning style and teaching style in an EFL classroom?. Issue 3 (26th May 2020) - Toyama, Michiko; Yamazaki, Yoshitaka
ABSTRACT: Purpose . This study aimed to explore whether a match between learning style and teaching style in English as a foreign language (EFL) class affects two student variables: proficiency and motivation to learn English. Design/methodology/approach . Participants consisted of nine EFL teachers and 331 Japanese undergraduate students who were required to take EFL courses. To examine learning style and teaching style, we applied the Kolb Learning Style Inventory and the Kolb Educator Role Profile, respectively. Findings . We created groups for student-teacher match and student-teacher mismatch (i.e., student's learning style vs. teacher's teaching style). The match group including four matched learning style–teaching style pairs was significantly related to proficiency and motivation, while the mismatch group including all other pairs was also significantly related to them. When further analysing the four constituent pairs within the match group, results varied in effect, depending on not only the pair of learning and teaching style but also the variables. Originality/value . This study was the first to examine how specific matched learning style–teaching style pairs affect proficiency and motivation. The results add to the literature on the mixed effects of matched versus mismatched styles, highlighting the complexity of the relationship and the possible reasons for some of the effects.